Evaluasi Risiko Kebangkrutan PT. Pratama Abadi Nusa Industri Tbk - Irawan, Via Mustika; Ningsih, Indah Sukma (CV. Kalimasada Group, 2024)
This research aims to reduce the risk of bankruptcy for PT. Pratama Abadi Nusa Industri Tbk, which is listed on the Indonesia Stock Exchange. Using a quantitative descriptive method with a case study approach, this research analyzes the company's financial reports from 2020 to 2022. The results of the analysis show a significant decline in activity turnover, extremes in the operating expense ratio, as well as volatility and losses in net profit. A decrease in current assets and an increase in liabilities indicate a serious liquidity problem. Overall, these findings indicate serious challenges in operational efficiency and cost management, which can hinder a company's ability to meet short-term obligations and maintain profitability. Strategis steps are needed from company management to improve financial conditions and restore investor confidence.